The 'other half' of the public debt–economic growth relationship: a note on Reinhart and Rogoff - Yannis Dafermos (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
Reinhart/Rogoff (2010) and Reinhart et al. (2012) document a negative relationship between public debt and economic growth. However, by classifying the observations of their data set into public debt categories and identifying public debt overhang episodes, they focus only on 'one half' of the public debt–economic growth relationship: the growth-reducing effects of high public debt. This note classifies the observations of their data set into economic growth categories and identifies low-growth episodes. In so doing, it presents the 'other half' of the public debt–economic growth relationship: the debt-increasing effects of low growth. It is argued that the presentation of 'both halves' is essential for a more fruitful research agenda and policy debate.
Keywords: E60; E62; H60; 330; public debt; economic growth